Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. The degree to which school principals practice the values of integrity from the point of view  of female deputies in Taif GovernorateCo-Prof. Saleha Hai Al-Sofiani2. The impact of online educational service quality on the reputation of Dubai University  during the COVID-19 pandemic from the perspective of studentsMr. Abdelmuttaleb Abdelsalam Elomari3. Teachers' and Parents' Attitudes Towards the Motives for Privatizing Education in Arab Private Schools in the Haifa and Upper Galilee AreasDr. Lubna Ali Elenat Khalaily4. Training needs for the Madrasati platform from the point of view of principals of general education schools in Al-Kharj GovernorateMs. Nouf Fahad Almuayli5. The extent to which the standards of the Commission for International Accreditation across regions (CITA) can be applied in leading schools in Jeddah from the perspective of leading school principalsDr. Majed Atteah Al-Sulami,Prof. Abdul-Hayy Ahmed Al-Subaihi6. Artificial Intelligence and its Impact on the Quality of English Language Teaching: An Applied Study on English Language Teachers in Primary Schools - Asir RegionMs. Aliah Mohammed Alahmari7. Anxiety as a Mediator between Procrastination and Work Engagement for AdministratorsMs. Alhanoof Mansour Alluhaidan., Dr. Ahmed Mohammed Ahmed Alhussein8. Emotional intelligence and its relationship to some variables among kindergarten teachers city of NajranDr. Nada Izzeldeen Jafar
Keywords: Journal of Educational and Psychological Sciences